Społeczno-kulturowe determinanty budowy organizacji innowacyjnych na przykładzie przedsiębiorstw usługowych - Brojak-Trzaskowska, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The author presents social and cultural barriers and stimuli' innovativeness of service enterprises. This article presents selected factors conditioning innovative activity of enterprises. It focuses on following elements: innovative organizational culture, learning processes, stimulating creative and innovative behaviours, concerning both units and employees groups. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 399-405